2022
DOI: 10.3389/fnmol.2021.773356
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Isoform-Specific Expression of CTBP2 Is Evolutionarily Conserved Between the Developing Chick and Human Retina

Abstract: Complex transcriptional gene regulation allows for multifaceted isoform production during retinogenesis, and novel isoforms transcribed from a single locus can have unlimited potential to code for diverse proteins with different functions. In this study, we explored the CTBP2/RIBEYE gene locus and its unique repertoire of transcripts that are conserved among vertebrates. We studied the transcriptional coregulator (CTBP2) and ribbon synapse-specific structural protein (RIBEYE) in the chicken retina by performin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Also, poly dT priming often introduces a 3’ bias for transcript characterization, particularly for long messages. Lastly, though the quantity of our reads depth in this study is below the threshold for rare isoform identification, there are enough reads per sample in our study to characterize abundant alternative mRNA isoforms as previously demonstrated [19] . Taking these considerations into account, these data will be a useful resource for the C. elegans community and others, providing a robust and accurate analysis of the polyadenylated transcriptional networks in nematodes exposed to varied bacterial pathogens.…”
Section: Limitationsmentioning
confidence: 85%
“…Also, poly dT priming often introduces a 3’ bias for transcript characterization, particularly for long messages. Lastly, though the quantity of our reads depth in this study is below the threshold for rare isoform identification, there are enough reads per sample in our study to characterize abundant alternative mRNA isoforms as previously demonstrated [19] . Taking these considerations into account, these data will be a useful resource for the C. elegans community and others, providing a robust and accurate analysis of the polyadenylated transcriptional networks in nematodes exposed to varied bacterial pathogens.…”
Section: Limitationsmentioning
confidence: 85%
“…A human induced pluripotent stem cell (hiPSC)-derived 3D retinal organoid system that mimics fetal human retinal development was used as previously described with authorization from the UC San Diego Institutional Review Board Committee 9 , 12 , 20 . The IMR90.4 iPSC line was obtained from WiCell (Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the data can be applied to compare gene regulation across species. For instance, we compared mRNA transcripts derived from embryonic chicken retinas to the RNA-seq reads from the current study and highlighted the conserved nature of transcriptional regulation of CTBP2/RIBEYE 20 . A recent report by Wahlin et al .…”
Section: Usage Notesmentioning
confidence: 99%
“…The RIBEYE/CtBP2 gene is a bi-functional gene and generates two gene products [18]. The CtBP2 promotor drives ubiquitous CtBP2 expression in most eukaryotic cells [18][19][20][21], whereas the RIBEYE promotor drives RIBEYE expression only in ribbon synapse-forming cells [12,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%